Associations between dietary fatty acids and kidney stones - Ning Tan; Ya Zhang (Scientific Reports)
Abstract Kidney stones represent a significant global health challenge, with dietary habits playing a crucial role in their formation. This study investigates the association between dietary fatty acid intake—specifically saturated (SFA), monounsaturated (MUFA), and polyunsaturated fatty acids (PUFA)—and the prevalence of kidney stones in a U.S. adult population, aiming to inform potential dietary prevention strategies. Data from the National Health and Nutrition Examination Survey (NHANES) spanning 2007–2018 were analyzed, including 30,716 participants. Logistic regression models were used to assess the relationship between fatty acid intake and kidney stones prevalence, adjusting for demographic and health-related covariates such as age, sex, BMI, diabetes status, physical activity, and other dietary factors. Additional analyses were conducted to explore the effects of fatty acid intake as a percentage of total energy and the impact of various fatty acid ratios. Higher intakes of SFA, MUFA, and PUFA were associated with increased odds of kidney stones prevalence. Specifically, each 10 g/day increase in SFA, MUFA, and PUFA intake was linked to a 22% [OR = 1.22, 95% CI: 1.11–1.34, p = 0.002], 10% [OR = 1.10, 95% CI: 1.00–1.22, p = 0.052] and 21% [OR = 1.21, 95% CI: 1.10–1.33, p = 0.001] higher odds of kidney stones, respectively. These associations were generally consistent across various subgroups. Additional analyses examining fatty acid intake as a percentage of total energy and various fatty acid ratios yielded compatible findings. The findings suggest a modest association between higher dietary fatty acid intake and increased odds of kidney stones prevalence. While the observed odds increases were relatively small, these results highlight the importance of considering dietary fatty acid types in kidney stones prevention strategies. Future research is needed to further elucidate the underlying mechanisms and to refine dietary recommendations.